P538 Enteral nutrition for the maintenance of remission in adults with inactive Crohn's disease: A meta-analysis. (16th January 2018) - Tang, W
Abstract: Background: Enteral nutrition for inducing remission of active CD is clear, and has been considered as the first-line therapy. However, the efficacy of enteral nutrition as maintenance of remission in patients with inactive CD has not been clarified yet. Methods: We searched several electronic databases (PubMed, EMbase, Cochrane Library, and Web of Science) from inception to December 2016 for applicable studies to identify relevant studies for review and analysis. Studies published in English were considered in this review. After a final set of studies was identified, the list of references reported in the included studies was reviewed to identify additional studies. Screening of titles and abstracts, data extraction, and quality assessment was undertaken independently. All the data were done using Review Manager 5.4 software and Stata 11.0 software. Results: A total of 1426 records were identified, 10 of which met the inclusion criteria. Seven of 10 presented data that could be used in quantitative analysis, and 3 could be used in qualitative analysis. The results of quantitative analysis showed that the OR of CD clinical relapse rates between EN and non-EN maintenance therapy for 12–24 months was 0.57 (95% CI 0.38–0.84, p = 0.005); The ORs of CD clinical remission rates between EN and non-EN maintenance therapy for 6, 12, 24, and 60 months were 1.24 (95% CI 1.01–1.52, P = 0.04), 1.56 (95% CI 1.26–1.92, p < 0.0001), 2.29 (95% CI 1.16–4.51, P = 0.02), 2.17 (95% CI 1.03–4.55, P = 0.04), respectively. The results of qualitative analysis showed that there was no significant difference in endoscopic recurrence rate between EN and non-EN maintenance therapy for 6 months ( p > 0.05), but a significant difference for 12 months ( p ＜ 0.05); There was no significant difference in the rate of CD remission between EN and 6-MP maintenance therapy for 12 and 24 months, respectively ( p > 0.05); In all three studies investigating impacts of the doses of EN on clinical remission, higher doses of EN were associated with higher remission rates: ≥30 kcal/kg ideal body weight/day (vs. <30 kcal/kg ideal body weight/day), ≥1200 kcal/day (vs. <1200 kcal/day), and＞900 kcal/day (vs. ≤900 kcal/day). Conclusions: The available data suggest that EN is more effective than non-EN for the maintenance of remission in adults with inactive CD, and even to maintain long-term remission. As the current studies are still less, the efficacy and long-term effects of EN as maintenance therapy for adult CD patients still require more, large sample, high quality randomised controlled trials to further confirm.